IMPROVING EMPLOYEE PERFORMANCE IN PUBLIC SERVICES THROUGH TRAINING: A CASE STUDY OF RUMAH SAKIT UMUM DAERAH (RSUD) CENGKARENG - Nina Kurnia (Adisam Publisher, 2024)
Services in the health sector are a real form of public service. Health is an investment for the country to carry out development because human resources who are physically and spiritually healthy are needed to realize national goals. However, until now, there are still many problems encountered in public services in the health sector. One effort to improve employee performance in public services is by holding training for employees. This research is aimed at answering the question of how training related to public services is implemented at RSUD Cengkareng and what obstacles are encountered in implementing this training. Data collection was carried out using semi-structured interviews with 15 employees at RSUD Cengkareng. The research results showed that the training carried out at RSUD Cengkareng consisted of internal training and external training, namely inviting instructors from professional training institutions. Training from training institutions held at RSUD Cengkareng is more effective if viewed from the materials, methods, quality of instructors, participants, infrastructure and training evaluation.